Celebrating David McLauchlan's Contribution - McLay, Geoff; Lynch, Nessa (Victoria University of Wellington Law Review, 2011)
This article serves as an introduction for this issue of the Victoria University of Wellington Law Review celebrating Professor David McLachlan's 40th anniversary as a faculty member. This foreword celebrates Professor McLachlan as one of the leading Commonwealth writers of contract law, as a colleague, and as a lecturer.